Cheap Ship Trips: A Preliminary Study of Some English Phonological Difficulties of Language-Minority Children and Their Relationship to Reading Achievement. Bilingual Education Paper Series, Vol. 7, No. 4 - Duncan, Sharon E (1983)
A study of the pronunciation problems of language-minority children had as subjects 578 first, third, and fifth-graders from seven ethnolinguistic groups (urban and rural Mexican-Americans, Puerto Ricans, Cuban-Americans, Franco-Americans, Native Americans, and Chinese-Americans) from low to low-middle income communities in California, Texas, Florida, New York, Louisiana, and New Mexico and 128 Anglo children from similar income groups. Results showed a significant positive relationship between phoneme production and reading achievement for some groups of third and fifth-graders, as well as for Anglo first-graders. The difficulty pattern varied across the ethnolinguistic groups, but the greatest pronunciation difficulty for the language-minority children was with the phonemes acquired last by first-language English speakers. While some phonological difficulties seem to disappear with increasing age for some groups, for others the difficulties are greater in the higher grades. (Author/MSE)